1998
DOI: 10.1006/jvlc.1998.0086
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Large Nested Graphs in 3D: Navigation and Interaction

Abstract: Most systems for visualizing large information structures use 2D graphics to view networks of nodes and arcs that represent data. To understand large structures it is often necessary to show both small-scale and large-scale structure. This has been called the problem of focus and context. Distortion, rapid zooming, elision, and multiple windows are all techniques that have been developed to provide both focus and context within single representations. We review these techniques and argue that 3D visualization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 14 publications
0
41
0
1
Order By: Relevance
“…In contrast, existing approaches (Section 6) primarily rely on multiple views when visualizing multiple aspects of a system [1,17,30,31]. Although multi-view approaches can be very effective, users may also have considerable difficulty managing and navigating through dif- ferent views [27,28,32]. In our current research, we are particularly interested in whether these difficulties can be overcome by judicious rendering within a single view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, existing approaches (Section 6) primarily rely on multiple views when visualizing multiple aspects of a system [1,17,30,31]. Although multi-view approaches can be very effective, users may also have considerable difficulty managing and navigating through dif- ferent views [27,28,32]. In our current research, we are particularly interested in whether these difficulties can be overcome by judicious rendering within a single view.…”
Section: Introductionmentioning
confidence: 99%
“…First, single-view illustrations avoid the difficulties when managing and navigating through different views [27,28,32]; secondly, they rapidly summarize a system because all information is available within that view; and thirdly, having one view helps different stakeholders to easily communicate different concerns within the same familiar picture. Single-view visualizations do not replace detailed stakeholder-specific visualizations.…”
Section: Practical Single-view Visualizationmentioning
confidence: 99%
“…Multiscale graph abstraction is another technique that preserves global structure, however navigation is difficult because clusters are explicitly contracted and expanded, e.g. [2,26]. Recent work combines these two approaches with topological fisheye views to reduce the number of displayed nodes while preserving the network structure [14].…”
Section: Related Workmentioning
confidence: 99%
“…However, several authors think that larger graph structures can be viewed in 3D (Parker et al (1998)). In the empirical study of Ware & Franck (1996), which measured path-tracing ability in 3D graphs, they suggested that the amount of information that can be displayed in 3D with stereoscopic and motion depth cues exceeds 2D representations by a factor of 3.…”
Section: Graphsmentioning
confidence: 99%